Critically Reviewing the Theory and Practice of Secured-by-design for Residential New-build Housing in Britain. - Cozens, Paul; Pascoe, T.; Hillier, David (Ashgate, 2007)
The Government has projected a need for some 4.1 million homes by 2021 (DETR, 1999a) and a stated policy objective of achieving 60% of new-build housing on 'brownfield' sites (DETR, 1999b). The government is clearly commited to 'designing out crime' (DOE, 1994, CDA, 1998) and this paper explores Secured By Design scheme (SBD), one of the most important community safety initiatives available to planners to assist in achieving these complex aims. The rise in premises' liability cases (Hanson, 1998) and the Human Rights Act, (HRA, 1998) illustrate the increasing importance of tackling such issues. A critical review of both the theory and practice of SBD is presented as it applies to the new-build residential environment in the British city. The implications of reviewing SBD's theoretical basis and its application are discussed.